The Portrayal of Beauty Myth in I Feel Pretty Movie (2018) - Afria Dian Prastanti; Adria Vitalya Gemilang; Inggit Yuniarsih Yuniarsih (LPPM Universitas Pekalongan, 2023)
The main object of this article is the movie script entitled I Feel Pretty. The purpose of this research are to find out the types of beauty myth portrayed by Renee as the main character in the movie and the influences of beauty myth on Renee in the movie. The researchers used the theory of beauty myth by Naomi Wolf to analyze the types of beauty myths portrayed by the main character in the movie. The theory of narrative and non-narrative by Boggs and Petrie was also used to analyze the aspects that influenced by the beauty myth of the main character in the movie. The method to analyze the data in this study is descriptive qualitative. To collect data, it was used two kinds of sources. The primary data of this study is taken from the movie script. The secondary data are taken from previous studies, books, journals, and other resource. In the results of this research, it was found the types of beauty myth portrayed by the main character namely beauty myth in work, beauty myth in culture, beauty myth in religion, beauty myth in sex, and beauty myth in hunger. It was also found the influence of the beauty myth on Renee as the main character, there are Renee's appearances and Renee's behavior. From the findings, it could be concluded that the beauty myth of Renee's life is complicated, both in her work and relationship.